Length of optic nerve double inversion recovery hypersignal is associated with retinal axonal loss. (April 2016) - Hadhoum, N; Hodel, J; Defoort-Dhellemmes, S; Duhamel, A; Drumez, E; Zéphir, H; Pruvo, JP; Leclerc, X; Vermersch, P; Outteryck, O
Objectives: To assess the association between optic nerve double inversion recovery (DIR) hypersignal length and retinal axonal loss in neuroinflammatory diseases affecting optic nerves. Methods: We recruited patients previously affected (> 6 months) by a clinical episode of optic neuritis (ON). We had 25 multiple sclerosis (MS) patients, eight neuromyelitis optica spectrum disorder (NMOSD) patients and two patients suffering from idiopathic caused ON undergo brain magnetic resonance imaging (MRI); including a 3-dimensional (3D) DIR sequence, optical coherence tomography (OCT) examination and visual disability evaluation. Evaluation criteria were retinal thickness/volume, optic nerve DIR hypersignal length and high/low contrast vision acuity. Results: In the whole cohort, we found good associations (< 0.0001) between optic nerve DIR hypersignal length, peripapillary retinal nerve fiber layer thickness, inner macular layers volumes, and visual disability. We found subclinical radiological optic nerve involvement in 38.5% of non-ON MS eyes. Conclusions: Optic nerve DIR hypersignal length may be a biomarker for retinal axonal loss, easily applicable in routine and research on new anti-inflammatory or neuroprotective drug evaluation. Detection of subclinical ON with 3D-DIR in a non-negligible proportion of MS patients argues in favor of optic nerve imaging in future OCT MS studies, in order to achieve a better understanding of retinal axonal loss in non-ON eyes.